Functional outcome of anterior cruciate ligament reconstruction in recreational and competitive athletes - Jerre, R.; Ejerhed, L.; Wallmon, A.; Kartus, J.; Brandsson, S.; Karlsson, J. (Scandinavian Journal of Medicine & Science in Sports, 2001)
The aim of this study was to compare the outcome after anterior cruciate ligament reconstruction in recreational and competitive athletes, with a minimum follow-up of two years. Forty-nine patients (24 males and 25 females) who, at the time of the index injury, were classified as recreational athletes (Tegner level 2-5) were compared with 226 patients (61 females and 165 males) who, at the time of the index injury, were classified as competitive athletes (Tegner level 9-10). At the follow-up, no significant differences were found between the study groups in terms of the Lysholm score, IKDC evaluation system, one-leg-hop test, KT-1000 laxity measurements, anterior knee pain and the patients' subjective evaluation of the results. However, the competitive athletes displayed a significantly higher reduction in Tegner activity level than the recreational athletes. The functional and objective results after anterior cruciate ligament reconstruction were comparable for the recreational and competitive athletes. We, therefore, conclude that anterior cruciate ligament reconstruction could be recommended for recreational athletes as well as competitive athletes.